Gain Enhancement of a Multiband Resonator Using Defected Ground Surface on Epoxy Woven Glass Material - Md. Shahidul Alam; Mohammad Tariqul Islam; Haslina Arshad (The Scientific World Journal)
A multiband microstrip resonator is proposed in this study which is realized through a rectangular radiator with embedded symmetrical rectangular slots in it and a defected ground surface. The study is presented with detailed parametric analyses to understand the effect of various design parameters. The design and analyses are performed using the FIT based full-wave electromagnetic simulator CST microwave studio suite. With selected parameter values, the resonator showed a peak gain of 5.85 dBi at 5.2 GHz, 6.2 dBi at 8.3 GHz, 3.9 dBi at 9.5 GHz, 5.9 dBi at 12.2 GHz, and 4.7 dBi at 14.6 GHz. Meanwhile, the main lobe magnitude and the 3 dB angular beam width are 6.2 dBi and 86°, 5.9 dBi and 53.7°, 8.5 dBi and 43.9°, 8.6 dBi and 42.1°, and 4.7 dBi and 30.1°, respectively, at the resonant frequencies. The overall resonator has a compact dimension of 0.52λ  × 0.52λ  × 0.027λ at the lower resonant frequency. For practical validation, a lab prototype was built on a 1.6 mm thick epoxide woven glass fabric dielectric material which is measured using a vector network analyzer and within an anechoic chamber. The comparison between the simulated and measured results showed a very good understanding, which implies the practical suitability of the proposed multiband resonator design.